(untitled) (Journal of Governance and Development (JGD), 2016)
The 2015 Nigerian general elections have come and gone. Though the election was scored high by local and international observers, it was not without flaws. The pre-election period witnessed one of the highest level of propaganda in the country. During this period, propaganda was at its peak as the PDP took advantage of its opportunities as the ruling party to spread negative messages about the opposition. However, while this large and well-orchestrated propaganda have been found successful in the past, the dominance of the PDP in the propagandistic war of the last election failed to produce the desired result. This study therefore sought to ascertain audience perception of the use of propaganda by PDP in the just concluded 2015 presidential election by examining the effectiveness of propaganda in political campaigns. Thus, premised on the theory of propaganda, this study surveyed 324 randomly selected respondents from the University of Ilorin. Data were analyzed using the Statistical Packages for Social Science (SPSS) and results were reported descriptively. Findings were discussed in details and suggestions for further studies were recommended.